Assessment Of Traffic Noise Level And Traffic Composition In Kulim, Kedah - Bakar, Mohd Faiz Abu (Universiti Sains Malaysia, 2021)
This study focuses on measuring the noise levels at the study area in Kulim, Kedah. There are 20 points selected around the area including Jalan Raya Kulim, Jalan Tunku Asaad, Jalan Tunku Putra dan Jalan Lunas. This study was carried out to identify the relationship between traffic noise levels and traffic composition in Kulim, Kedah. Decibel-X Pro application was used to record the noise levels for 15 minutes for the morning, afternoon and evening period. The noise level measurements were monitored in the morning (0800-0930), afternoon (1200-1400) and evening (1400-1530). The traffic density was manually counted simultaneously with noise level measurement according to Arahan Teknik Jalan (8/86), A Guide on Geometric Design of Roads (cars, light vans, motorcycle, small lorries and heavy lorries). The average sound level (LAeq) obtained at the areas ranging from 55 dB(A) until 65 dB(A). All the sound level (LAeq) recorded exceeded the maximum permissible sound level (LAeq) according to the Planning Guidelines for Receiving Land Use for Planning and New Development for Environmental Noise Limits and Control by the Department of Environment. This study proved that there are various relationship between traffic noise levels and traffic composition which show that the noise levels decreases when the traffic composition increases and also the other way round. This event influenced by the difference speed of the vehicles and the noise produced by each vehicle is different.